2020
DOI: 10.1186/s12886-020-01424-x
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic manifestations of congenital protein C deficiency: a case report and mini review

Abstract: Background: Homozygous protein C (PC) deficiency is a potentially fatal disease with ocular blinding presentation or sequela. Case presentation: A 5 month-old boy was presented for evaluation of leukocoria. He had a history of frequent bruises and PC deficiency, treated with warfarin. His intraocular pressure was normal. In the left eye leukoma with anterior segment dysgenesis, shallow anterior chamber, and cataract were observed. Fundus was not visible. B-scan revealed a closed funnel retinal detachment. His … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…10 There are many case reports of retinal artery thrombosis or branch retinal artery thrombosis due to protein C deficiency. 23 This case is unique because most of the case reports showed that Protein S deficiency is associated with venous and cerebral thrombosis followed by coronary circulation. However, retinal artery thrombosis due to Protein S deficiency is very rare.…”
Section: Discussionmentioning
confidence: 95%
“…10 There are many case reports of retinal artery thrombosis or branch retinal artery thrombosis due to protein C deficiency. 23 This case is unique because most of the case reports showed that Protein S deficiency is associated with venous and cerebral thrombosis followed by coronary circulation. However, retinal artery thrombosis due to Protein S deficiency is very rare.…”
Section: Discussionmentioning
confidence: 95%
“…Ghassemi et al reported a patient that had congenitally deficiency in pro C and presented with ocular manifestations. They suggested that protein C deficiency should be evaluated in all children with leukocoria because early detection can save their eyesight [5] .…”
Section: Discussionmentioning
confidence: 99%
“…There have been previous reports of protein C deficiency, presenting with neonatal purpura fulminans; intracranial hemorrhage or infarctions; and ophthalmologic complications including non-reactive pupils; leukocoria; vitreous, retinal, and subretinal hemorrhage; retinal arterial and venous occlusion; kidney infarction; and rarely, colonic perforation [ 1 , 9 , 10 ]. In most cases, treatments such as FFP replacement, LMWH, warfarin, and protein C concentrates were used effectively.…”
Section: Discussionmentioning
confidence: 99%